1998
DOI: 10.1029/98gl00642
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic deformation of Etna Volcano observed by satellite radar interferometry

Abstract: Abstract. Satellite radar interferometry of Mt. Etna volcano, Sicily, Italy, reveals a sequence of deformation characterized by deflation during the end of the 1993 eruption, inflation from 1993-1995 with an increase in the inflation rate immediately before its resumed eruptive activity in late 1995. This was followed by very low deformation levels during the following year. The source of the deformation changed from a depth of 9 km during deflation to more than 11-14 km during the subsequent inflation, consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 14 publications
4
52
1
Order By: Relevance
“…Centimeter-scale ground deformation attributed to magma movement, particularly in periods immediately preceding or following an eruption, is well established in a number of previous studies [1,4,[56][57][58][59]. At Augustine, however, magma source-related deformation has been subtle and at or below the detection level of geodetic systems for most of its recent history.…”
Section: Geophysical Considerations and Model Assumptionsmentioning
confidence: 88%
“…Centimeter-scale ground deformation attributed to magma movement, particularly in periods immediately preceding or following an eruption, is well established in a number of previous studies [1,4,[56][57][58][59]. At Augustine, however, magma source-related deformation has been subtle and at or below the detection level of geodetic systems for most of its recent history.…”
Section: Geophysical Considerations and Model Assumptionsmentioning
confidence: 88%
“…DInSAR has been successfully demonstrated in many applications, such as monitoring volcanic activity (Lanari et al 1998), determination of glacier movement (Goldstein et al 1993), measuring earthquake or seismic related deformation Ge et al 2009) and monitoring underground mining activity Ge et al 2007). But DInSAR results are limited by the decorrelation and atmospheric artefacts, thus restricting assessment of ground movement to a relatively short period.…”
Section: Introductionmentioning
confidence: 99%
“…After this correction and by again using a simple Mogi source, they obviously find a deflation source at a shallower depth with respect to the one proposed by MASSONET et al (1995). LANARI et al (1998), by applying a grid search method of inversion and without performing any tropospheric correction, found that some interferograms of the considered period are fit well by a point source located at a 9 km depth. It has also been noted (CAYOL and CORNETTE, 1998;WADGE, 1998, 2000) that topography could play a role in the computation of the surface displacement for a given source and, therefore, should be accounted for in the deformation source modelling process; this was not considered in the previously cited works.…”
Section: Previous Deformation Models At Mt Etna For 1991-1993 Deflationmentioning
confidence: 99%